(untitled) (FAN, TA’LIM, TEXNOLOGIYA VA ISHLAB CHIQARISH INTEGRATSIYASI ASOSIDA RIVOJLANISH ISTIQBOLLARI, 2025)
This article explores the concept of word stress in English, explaining its importance in communication and how it affects the clarity and meaning of words. It highlights the role of word stress in distinguishing between different parts of speech, such as nouns and verbs (e.g., REcord vs. reCORD), and discusses the rhythm of English as a stress-timed language. The article also outlines common stress patterns in nouns, verbs, adjectives, and compound words, and offers practical advice for learners on how to master word stress. Techniques such as listening, imitation, using a dictionary, and practicing with minimal pairs are suggested for improving pronunciation. The article concludes by emphasizing the role of word stress in achieving effective and fluent English communication.